Implementasi Penggunaan Metode Sosiodrama Pada Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VIII di MTs Aswaja Tunggangri - Nadya Rifa’atul Kanin; Nur Isroatul Khusna (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This research aims to find out the planning stage of using the sociodrama method in social studies subjects in class VIII at MTs Aswaja Tunggangri. The method used is descriptive qualitative. The data obtained is through interviews, observation, and documentation. Data analysis techniques with steps including data condensation, presenting data, and drawing conclusions. The results of this study show that before the learning process is carried out, it is necessary to prepare a learning plan including preparing lesson plans in accordance with the syllabus, determining learning objectives, determining teaching materials and learning resources, adjusting learning methods, and preparing assessments, the implementation stage is providing stimulus to students, identifying problems, collecting data, processing data, proving, drawing conclusions, evaluating the sociodrama method, namely attitude evaluation, knowledge evaluation, and skill evaluation. This finding indicates that the design before conducting learning is very influential on the achievement of learning objectives.